Efficacy of S-PRG filler containing varnishes on enamel demineralization prevention - Spinola, Manuela da Silva [UNESP]; Moecke, Sabrina Elise [UNESP]; Rossi, Natália Rivoli [UNESP]; Nakatsuka, Toshiyuki; Borges, Alessandra Bühler [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Springer Nature, 2020)
This study evaluated the efficacy of S-PRG vanishes on preventing enamel demineralization. Bovine enamel specimens were obtained, polished and the baseline Knoop microhardness was evaluated. Specimens were stratified into six groups (n = 15), according to the varnish applied: S10—experimental varnish containing 10% of S-PRG fillers, S20—20% of S-PRG fillers, S30—30% of S-PRG fillers; S40—40% of S-PRG fillers; PC (positive control)—5% of NaF; NC (negative control)—no treatment was performed. Half of enamel surfaces were protected to work as a control and varnishes were applied over the unprotected area. A demineralizing pH-cycling was performed, and surface and cross-sectional microhardness were measured. The percentage of microhardness of the treated area was calculated comparing with the untreated area. Statistical analysis was performed by one-way ANOVA and Tukey’s test (p = 5%). All experimental S-PRG varnishes protected against demineralization in relation to no treatment, but S40 was the most effective on the surface. For all depths, S30 and S40 were superior in enamel demineralization prevention than other S-PRG filler concentrations and 5% NaF. It was concluded that S-RPG filler containing varnishes were effective to prevent enamel demineralization. The higher concentrated products were more effective than 5% sodium fluoride on surface demineralization prevention.